Assessment of Lactoferrin Concentration in Human Milk and Survey on it's Relation with Age, Child Birth Time, and after Child Birth - S Nasirinejad; M Noruzi; MB Eslami; A Salehinodeh; M Fazli; GH Hassan pour (Tehran University of Medical Sciences, 2009)
Background and Aim : Lactoferrin is one of the milk components with the main role in iron absorption and transfer. As a result of this action the pathogens that need iron for their life cannot grow, so the infection will be controled, indirectly. Moreover, because the lactoferrin production is stopped in the women with breast cancer, evaluation of this protein in milk may be the first step in detection of breast cancer tumors, and making decision about the appropriate treatment methods. Therefore, with due attention to the important role of lactoferrin in health and disease, determination of its normal dose in milk is very essential for the differences that may occur comparing with the normal situation. Also since the normal amount of lactoferrin in the milk of Iranian women was not evaluated; in this study the amount of protein in more than 100 sample was measured.Materias and Methods: The lactoferrin amount was measured by SRID method in 104 human milk samples of mothers that were referred to two public health centers in Tehran for vaccination of their children, and also in women that were hospitalized after childbirth in 2 health centers of Qom city. The data such as age, time of childbirth, etc were obtained by asking them and filling pre-designed questionnaire. All laboratory experiments were conducted in the Immunology unit of pathobiology department of School of Public Health, Tehran University of Medical Sciences.Results: The mean concentration of lactoferrin was 4.39 g/L, in the early milk (6-10 days after childbirth) was 3.79 g/L and in the mature milk (11-60 days after childbirth) measured as 2.45 g/L.Discussion and Conclusion: The mean concentration of Lactoferrin in milk (g/L) has a significant difference with the day after childbirth (P<0.05) and was highest in Colostrums and then in primary milk. After that this amount is reduced extremely. This indicates the important role of lactoferrin in the primary days of infants, because of the protective role that it has against infections. Also the results of this study showed no significant correlation between human milk and factors such as age and childbirth time.